Profitability change in the global airline industry - Scotti, Davide; Volta, Nicola (Elsevier, 2017)
This paper studies airline profitability change computed through a Bayesian estimation of a cost function. The stochastic frontier is applied to a dataset including the largest worldwide airlines in the period 1983–2010. We show that productivity change is mainly driven by technical change becoming continuously positive from early 1990s. Furthermore, in the last decade profitability change is mainly driven by input price change which exhibits a similar pattern to output price change. In presence of productivity growth, the output price increase is lower than the input price increase suggesting that part of productivity gains are transferred from airlines to consumers
Keywords: Airline; Profitability; Cost function; Decomposition; Efficiency